If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-2g + -8) = 24 Reorder the terms: 2(-8 + -2g) = 24 (-8 * 2 + -2g * 2) = 24 (-16 + -4g) = 24 Solving -16 + -4g = 24 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -4g = 24 + 16 Combine like terms: -16 + 16 = 0 0 + -4g = 24 + 16 -4g = 24 + 16 Combine like terms: 24 + 16 = 40 -4g = 40 Divide each side by '-4'. g = -10 Simplifying g = -10
| (x+8)2=49 | | 1.4=7a | | -2/11=b/50 | | 4x+1=2(-2x-3) | | 1.4x+14.32=2.35x+21.92 | | 11-9x=43-23x | | 10(x+2)=3(x-5) | | 5x-25=225 | | 6x+2x=10x+12-4 | | -8r-3(6-2r)+48=30 | | 6r=.42 | | 80-5x=8x-15 | | 3(-2/3)-4(1/2)= | | -3+6x=5x-14 | | 4(d+7)=88 | | 3a+7-5a=-11 | | 3r=1.2 | | 3w+17=8 | | 9(x-3)=16 | | -10-5x=5x-10 | | 3(p+2)+2(p-3)=-5 | | 200=a+b | | 275-5x=40x+15 | | 6x+3(4-x)=8-2(x+3) | | 13-8x=141-36x | | -7x+3(-2x-11)=-98 | | n+n-7=33 | | 2n-9=53 | | 100x-670=-670 | | (ax^3-3x^2+2bx-2)-(2x^3-cx^2-5x-4d)=x^2+x-6 | | 2x-3(4x-11)=143 | | -k+11(-k-0.01)= |